2013
DOI: 10.1182/blood-2012-07-443770
|View full text |Cite
|
Sign up to set email alerts
|

Anagrelide compared with hydroxyurea in WHO-classified essential thrombocythemia: the ANAHYDRET Study, a randomized controlled trial

Abstract: Key Points Noninferiority of anagrelide in comparison with hydroxyurea in WHO-essential thrombocythemia, a phase 3 trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
229
7
13

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(267 citation statements)
references
References 42 publications
18
229
7
13
Order By: Relevance
“…In addition, adverse dropout rate was significantly higher in the anagrelide arm. In the second study [102], anagrelide was compared to hydroxyurea in 259 high-risk ET patients; during the total observation time of 730 patient-years, there was no significant difference between the anagrelide and hydroxyurea group regarding incidences of major arterial (7 vs. 8) and venous (2 vs.6) thrombosis, severe bleeding events (5 vs. 2), minor arterial (24 vs. 20) and venous (3 vs. 3) thrombosis and minor bleeding events (18 vs. 15), or discontinuation rates (adverse events 12 vs. 15 or lack of response 5 vs. 2); incidences of leukemic or fibrotic transformations were not reported. It should be noted that WHO diagnostic criteria were strictly adhered to in the latter study [102] and not in the former [89].…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, adverse dropout rate was significantly higher in the anagrelide arm. In the second study [102], anagrelide was compared to hydroxyurea in 259 high-risk ET patients; during the total observation time of 730 patient-years, there was no significant difference between the anagrelide and hydroxyurea group regarding incidences of major arterial (7 vs. 8) and venous (2 vs.6) thrombosis, severe bleeding events (5 vs. 2), minor arterial (24 vs. 20) and venous (3 vs. 3) thrombosis and minor bleeding events (18 vs. 15), or discontinuation rates (adverse events 12 vs. 15 or lack of response 5 vs. 2); incidences of leukemic or fibrotic transformations were not reported. It should be noted that WHO diagnostic criteria were strictly adhered to in the latter study [102] and not in the former [89].…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 95%
“…In the second study [102], anagrelide was compared to hydroxyurea in 259 high-risk ET patients; during the total observation time of 730 patient-years, there was no significant difference between the anagrelide and hydroxyurea group regarding incidences of major arterial (7 vs. 8) and venous (2 vs.6) thrombosis, severe bleeding events (5 vs. 2), minor arterial (24 vs. 20) and venous (3 vs. 3) thrombosis and minor bleeding events (18 vs. 15), or discontinuation rates (adverse events 12 vs. 15 or lack of response 5 vs. 2); incidences of leukemic or fibrotic transformations were not reported. It should be noted that WHO diagnostic criteria were strictly adhered to in the latter study [102] and not in the former [89]. Most recently, ruxolitinib (a JAK1 and JAK2 inhibitor) was compared to best available therapy (BAT) in 222 patients with hydroxyurea resistant or intolerant PV with splenomegaly [103]; the primary endpoint, which was control of hematocrit and splenomegaly, although significantly better than that of BAT, was achieved in only 21% of ruxolitinib-treated patients and there was no evidence of disease-modifying activity.…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 95%
“…59 More recently, the ANAHYDRET study concluded that anagrelide is not inferior compared with hydroxyurea in the prevention of thrombotic complications in patients with ET diagnosed according to the 2008 WHO criteria. 7 The US Food and Drug Administration (FDA) has approved anagrelide for the treatment of ET, whereas the European Medicine Agency (EMA) has been more restrictive, approving the drug for treatment of patients with high-risk ET who are intolerant to their current therapy or whose elevated PLT counts are not reduced to an acceptable level by their current therapy. An expert panel has provided a definition of clinical resistance/ intolerance to hydroxyurea in ET.…”
Section: How We Treat Patients With Et According To Their Individual mentioning
confidence: 99%
“…1,2 In the last few years, there have been significant advances in our understanding of the genetic basis, pathophysiology, and clinical course of ET. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Our article aims to offer up-to-date information and guidance regarding diagnosis and treatment of ET patients. To provide directions in the therapeutic management of common or complex clinical situations of the disease,…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that claim the superiority of cytoreductive treatment with HU combined with aspirin in comparison with anagrelide combined with aspirin in reduction of thrombotic events and lowering leukocytes, in ET [19,20]. However, non-inferiority of anagrelide in preventing ET-related events was demonstrated in a prospective study conducted by Gisslinger et al [21].…”
Section: Discussionmentioning
confidence: 99%